Human Dignity Conference - Part 1
Speeches recorded at the international conference in honor of outgoing Hungarian President Árpád Göncz held at the Hungarian Academy of Sciences in Budapest. The conference, entitled "On Human Dignity," was organized by the Hungarian Academy of Sciences, Central European University and the Faculty of Law and Political Science of Eötvös Loránd University. The audio cassette contains the recorded speeches of the chairman of the conference, the Nigerian writer Wole Soyinka, Romanian philosopher Andrei Pleşu, economist and philanthropist George Soros, and Katalin Gönczöl, the past first Parliamentary Commissioner for Human Rights (Ombudsman) of Hungary.